Aurangzeb Alamgir on Inter Faith Harmony - Muhammad Riaz Mahmood; Muhammad Irfan Ahmad; Hafiz Adil Jahangir (Journal of Islamic Thought and Civilization, 2019)
Islam provides an absolute religious freedom to the followers of all the religions. The Muslims promoted peace, mutual respect, inter-faith harmony and religious equality in the Sub-Continent in this ideological prospective. The Mughal rulers not only continued this glorious Islamic tradition but also promoted it on a very large scale. Aurangzeb Alamgir is one of those Mughal rulers who not only granted religious freedom to the non-Muslim inhabitants of India rather he honored many non-Muslims especially the Hindus with important public offices. He took special steps for their comprehensive socio-religious welfare and progress. He not only provided security to the contemporary religious worship places of the non-Muslims, but also allowed them to build new religious as well as educational institutions where they wanted. Contrary to the historical facts, some of the partial writers accuse Aurangzeb Alamgir to be prejudiced and cruel towards his non-Muslim subjects, particularly the Hindus. They think that Aurangzeb Alamgir demolished the Hindu temples as well as the Hindu schools. He increased the amount of “Jizya”, took some steps for forced religious preaching and the Hindus were expelled from public services and official posts. But, these allegations do not match the historical realities. This research article aims to conduct a thorough and an impartial analysis of these allegations.